The impact of caring for COVID-19 patients on nurse professional identity: A cross-sectional study using propensity score analysis - Tong, Lai Kun; Zhu, Ming Xia; Wang, Si Chen; Cheong, Pak Leng; Van, Iat Kio (Frontiers in Public Health, 2022)
Objective To examine the impact of caring for COVID-19 patients on the professional identity of nurses. Methods An online survey was conducted between 19 May and 7 August 2020 in 11 Chinese cities, including Dongguan, Foshan, Guangzhou, Hong Kong, Huizhou, Jiangmen, Macao, Shenzhen, Zhaoqing, Zhongshan, and Zhuhai. Propensity score matching was used to adjust for confounding variables between nurses with and without experience caring for COVID-19 patients. To analyze the impact of caring for COVID-19 patients on nurses' professional identity, a nominal logistic regression model was used rather than an ordinal regression model because the parallel regression assumption was violated. Results After propensity score matching, the final sample contained 1,268 participants, including 634 nurses who cared for COVID-19 patients. During the COVID-19 outbreak, 88.6% of nurses had high levels of professional identity. Nurses who cared for COVID-19 patients had the lowest percentage of high score level on the professional identity subscale for “sense of organizational influence,” as did nurses who did not care for COVID-19 patients. The findings indicated that nurses who cared for COVID-19 patients were 17.95 times more likely to have a high professional identity than a low professional identity (95% CI 2.38–135.39, p = 0.005), after completely controlling for the other factors. There were significant differences between nurses who cared for COVID-19 patients and those who did not in scores on the subscales of professional identity, except for the subscales “sense of self-decision-making” (χ2 = 4.85, p = 0.089) and “sense of organizational influence” (χ2 = 4.71, p = 0.095). Conclusion Nurses' professional identity is positively impacted by their experience caring for COVID-19 patients. Caring for COVID-19 patients should be highlighted as an opportunity to enhance nurses' professional identity. To further enhance the professional identity of nurses, we call for visible nursing leadership during the COVID-19 pandemic and improve their working environment.